Focused ion beam-SEM 3D analysis of mineralized osteonal bone: lamellae and cement sheath structures. (February 2021) - Raguin, Emeline; Rechav, Katya; Shahar, Ron; Weiner, Steve
Abstract: The mineralized collagen fibril is the basic building block of bone, and hence is the key to understanding bone structure and function. Here we report imaging of mineralized pig bone samples in 3D using the focused ion beam-scanning electron microscope (FIB-SEM) under conditions that reveal the 67 nm D-banding of mineralized collagen fibrils. We show that in adult pig osteons, the lamellar bone comprises alternating layers with either collagen fibrils predominantly aligned in one direction, and layers in which fibrils are predominantly aligned in two directions. The cement sheath contains thin layers of both these motifs, but its dominant structural component comprises a very complex layer of fibrils predominantly aligned in three or more directions. The degree of mineralization of the cement sheath is comparable to that of the osteon interior. The extent of alignment (dispersion) of the collagen fibrils in the osteonal lamellar bone is significantly higher than in the cement sheath. Canaliculi within the cement sheath are mainly aligned parallel to the cement sheath boundary, whereas in the lamellar bone they are mainly aligned perpendicular to the lamellar boundaries. This study further characterizes the presence of two types of collagen fibril arrangements previously identified in demineralized lamellar bone from other species. The simple sample preparation procedure for mineralized bone and the lower risk of introducing artifacts opens the possibility of using FIB-SEM to study more samples, to obtain automatic quantitative information on collagen fibril organization and to evaluate the degrees of mineralization all in relatively large volumes of bone. Graphical abstract: Image, graphical abstract